Regionalism in Standards: Good or Bad for Trade? - Chen, Maggie Xiaoyang (2012)
Regional agreements on standards have been largely ignored by economists and blessed by multilateral trade rules. Using a constructed panel data that identifies the different types of agreements at the industry level, we find that such agreements increase the trade between participating countries but not necessarily with the rest of the world. Harmonization of standards may reduce the exports of excluded countries, especially in markets that have raised the stringency of standards. Mutual recognition agreements are more uniformly trade promoting unless they contain restrictive rules of origin, in which case intra-regional trade increases at the expense of imports from other countries.